Kajian Literatur: Mengungkap Faktor-Faktor Yang Mempengaruhi Kebijakan Dividen Perusahaan - Eka Yuliyanti; Anis Turmudhi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this literature review is to examine the factors that influence dividend policy. This study reviews existing literature on dividend policy and identifies several factors that affect a company's decision to pay dividends. These factors include profitability, liquidity, free cash flow, firm size, leverage, company life cycle, and asset turnover. This study finds that these factors interact with each other and affect a company's ability to pay dividends. The findings of this study provide insights for companies to develop effective dividend policies that balance investor interests and financial performance. This study also highlights the limitations of existing research and suggests avenues for future research.